Art Studio as Preservation Engine: Performance Art Conservation Management Strategies in Purworejo Regency - Adhitya Darmantho; Maria Magdalena Cita Hapsari (Journal of Linguistica, 2024)
Performing arts, as the highest manifestation of human creative wisdom, reflect the soul and cultural identity of a nation. In Indonesia, performing arts not only mirror diversity but also are deeply rooted in cultural sustainability. However, traditional arts are fragile in the era of modernity, facing challenges of continuity and extinction. Preservation efforts become an eternal call, with art studios becoming loci for cultural preservation and transformation. Research in the Purworejo region emphasizes the importance of preserving traditional arts in both local and global contexts, reinforcing the spirit of unity in cultural diversity. This research employs a qualitative approach using literature review methods. Saripurnomo Art Studio and Prigel Art Studio in Purworejo Regency employ management strategies to preserve traditional arts. Saripurnomo Art Studio recruits the younger generation to uphold Incling art and promote it through activities and social media. Prigel Art Studio modifies Dolalak dance while maintaining traditional values through adaptation, including collaboration with the government to support its continuity.